Combined Exposure of Activated Intestinal Epithelial Cells to Nondigestible Oligosaccharides and CpG-ODN Suppresses Th2-Associated CCL22 Release While Enhancing Galectin-9, TGFβ, and Th1 Polarization - Saskia A. Overbeek; Atanaska I. Kostadinova; Martine A. Boks; Simone M. Hayen; Wilco de Jager; Belinda van’t land; Leon M. Knippels; Johan Garssen; Linette E. M. Willemsen (Mediators of Inflammation)
Background. Short-chain galacto- and long-chain fructo-oligosaccharides (scGOS/lcFOS) and CpG-ODN affect intestinal epithelial cells (IEC). Epithelial IL1α may contribute to allergic sensitization via autocrine mediator release affecting dendritic cells (DC). We studied whether IL1α contributes to Th2-associated mediator release by activated IEC and IEC/DC cocultures and possible modulation by scGOS/lcFOS±CpG-ODN. Methods. Solid phase or transwell cultured IEC were preincubated with IL1α and/or IFNγ/TNFα for 6 h. The transwell IEC were also apically exposed to scGOS/lcFOS±CpG-ODN for 6 h, washed, and re-exposed, while cocultured with immature moDC (ccDC) for 48 h. These ccDC were subsequently added to allogeneic naïve T cells (MLR). IEC- and/or DC-derived mediators and T cell cytokines were measured. Results. IL1α tended to enhance IL25 and enhanced IL33 and CCL20 release by IEC, while IL1α or TNFα or IFNγ enhanced CCL22. These were all further increased upon combined exposure of IFNγ/TNFα±IL1α coinciding with increased IL33 secretion in the solid phase culture. In the transwell, IL25 and IL33 remained under detection, while CCL20 and CCL22 were induced by IL1α or IFNγ/TNFα, respectively, and a synergistic increase was observed upon combined exposure of IFNγ/TNFα and IL1α. Furthermore, IFNγ was found to enhance galectin-9 secretion, which was more pronounced in IFNγ/TNFα±IL1α-exposed IEC and coincided with TGFβ increase. Epithelial CpG-ODN exposure further increased CCL20, while reducing CCL22 release by IFNγ/TNFα/IL1α-activated IEC; however, scGOS/lcFOS suppressed both. Combined scGOS/lcFOS and CpG-ODN reduced CCL22, while CCL20 and regulatory galectin-9 and TGFβ remained high in the supernatant of IFNγ/TNFα/IL1α-activated IEC and the following IEC/DC coculture. ccDC of scGOS/lcFOS- and CpG-ODN-exposed IFNγ/TNFα/IL1α-activated IEC increased IFNγ, IL10, TGFβ, and galectin-9 secretion in the MLR compared to ccDC exposed to control-activated IEC. Conclusion. IL1α enhanced CCL20 and Th2-associated CCL22 release by IFNγ/TNFα-activated IEC. Combined scGOS/lcFOS and CpG-ODN exposure suppressed CCL22, while maintaining high CCL20, TGFβ, and galectin-9 concentrations. In addition, ccDC derived from this IEC/DC coculture enhanced Th1 and regulatory mediator secretion mimicking known in vivo effects.